1993
DOI: 10.1007/bf02072030
|View full text |Cite
|
Sign up to set email alerts
|

In vitro kinetics of styrene and styrene oxide metabolism in rat, mouse, and human

Abstract: Styrene oxide (SO), a labile metabolite of styrene, is generally accepted as being responsible for any genotoxicity associated with styrene. To better define the hazard associated with styrene, the activity of the enzymes involved in the formation (monooxygenase) and destruction of SO (epoxide hydrolase and glutathione-S-transferase) were measured in the liver and lungs from naive and styrene-exposed male Sprague-Dawley rats and B6C3F1 mice (three daily 6-h inhalation exposures at up to 600 ppm styrene) and Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 33 publications
5
37
1
Order By: Relevance
“…sible through a reciprocal Lineweaver-Burk plot of the data, which unevenly weighs data points and masks non-Michaelis-Menten behavior. For comparison to previous studies (Mendrala et al, 1993;Nakajima et al, 1994;Wenker et al, 2001), we recast data from our microsomal reactions as a Lineweaver-Burk plot shown in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sible through a reciprocal Lineweaver-Burk plot of the data, which unevenly weighs data points and masks non-Michaelis-Menten behavior. For comparison to previous studies (Mendrala et al, 1993;Nakajima et al, 1994;Wenker et al, 2001), we recast data from our microsomal reactions as a Lineweaver-Burk plot shown in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…This degradative pathway occurs very slowly in water but is rapidly catalyzed by epoxide hydrolase. CYP2E1 is primarily responsible for the initial critical step in styrene activation to a reactive metabolite (Mendrala et al, 1993;Nakajima et al, 1994;Kim et al, 1997;Wenker et al, 2001), and thus, an understanding of the contribution of CYP2E1 to the metabolic clearance of styrene is necessary for adequately estimating risk associated with exposure to this pollutant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar type of dose-response curve was also reported by Osterman-Golkar et al (1999, investigat-ing the adduct formation in haemoglobin of mice exposed to these compounds. This sublinearity can indicate the saturation of styrene oxide detoxification at higher doses, possibly as a result of the saturable activity of glutathione transferase (Mendrala et al 1993). It also appears that the further metabolism of styrene oxide is saturable.…”
Section: Discussionmentioning
confidence: 99%
“…The ep oxide is detoxified by epoxide hydrol ase. Mendrala et al (15) reported that the ac tivity of the epoxi de hyd rolase relative to mon oo xygenase ac tivity was much greater in hum an liver than in mou se liver. Th e apparent half-time for styrene-7,8-oxi de in mouse and human wa s calculated to be 38 and 1.8 min, resp ectivel y.…”
Section: Discussionmentioning
confidence: 99%